PSEUDO-BATTLE OF MEMORY: DUA MEMORI KOLEKTIF PANGERAN SAMUDRO DI GUNUNG KEMUKUS - Prasadana, Muhammad Anggie Farizqi (Balai Pelestarian Kebudayaan Wilayah X, 2018)
Objek wisata Gunung Kemukus sesungguhnya mengandung dua memori kolektif tentang Pangeran Samudro. Kendati demikian, keduanya tidak dapat berjalan bersama, tetapi justru saling bertarung dan mengalahkan satu sama lain, sehingga hanya satu memori yang menjadi pemenang dan berkembang luas. Permasalahan penelitian ini adalah mengungkapkan awal mula terciptanya kedua ingatan tentang Pangeran Samudro. Selain itu menjelaskan mengapa dalam perkembangan selanjutnya salah satu dari keduanya mendominasi yang lain, serta mengapa pertarungan di antara keduanya disebut sebagai pertempuran memori yang semu.____________________________________________________________Mount Kemukus tourism object has two collective memories about Prince Samudro. However, the two memories fight and defeat each other. This study aims to find out how those two memories battle. This study used qualitative methods and qualitative descriptive analysis. The results showed that initially there was only one collective memory of Prince Samudro who was passed down from generation to generation in Mount Kemukus. Since Mount Kemukus is increasingly crowded with residential settlements, a second memory emerges which on the basis of economic interests seeks to defeat the memory that had already existed. In the next development, the second memory is actually developing because of offering a pilgrimage procession on Prince Samudro’s grave, which is easier in the form of sexual intercourse. The first memory does not remain silent and attempts to subdue the second memory. However, the first memory battle against the second memory was only half-hearted.